RIGHT TO HAVE RIGHTS - Michael, Tomy (Mimbar Keadilan, 2017)
Right is the basic essentials that can make legislation run well. But every practice of right always causes some legal issues. It means that the practice of every human in Indonesia can have right to have rights is not used yet, because of the exist of Pancasila. Indonesia needs to care more about this, that every citizen must have their right to have rights, as long as the right is not divide the unity and integrity of the nation of Indonesia. Whatâs mean with the right that Indonesian people must get is about right to live or death, right to choose their own religion, or right to choose their sex.Keywords: rights, interpretation, to have right